Men writing eating disorders : autobiographical writing and illness experience in English and German narratives - Bartel, Heike (Emerald Publishing Limited, 2020)
Eating disorders do not only affect women and girls; men and boys get them too but remain mostly invisible. This book gives insight into this neglected problem through a comparative and transnational analysis of autobiographical accounts written by men with experience of living with eating disorders.
Includes index.
Keywords: English literature -- Male authors -- History and criticism.; German literature -- Male authors -- History and criticism.; Autobiography.; Eating disorders in men.; Eating disorders in literature.; Masculinity in literature.; Mental illness in literature.; Literary Collections -- European / English, Irish, Scottish, Welsh.; Literary studies: fiction, novelists & prose writers.; elektronické knihy; electronic books